Regional pattern of cardiovascular risk burden in Croatia - Kern, Josipa (Array, 2009)
Summary: The objective of this study was to investigate regional gradient of a synthetic cardiovascular burden (CVRB) in Croatia. Analysis was based on a multistage stratified sample representative of general adult population in six regions of Croatia (Croatian Adult Health Survey). Synthetic CVRB was defined by incidents (heart attack, stroke), blood pressure, overweight/obesity (BMI, waist circumference), and risky behaviours (smoking, physical inactivity, high alcohol consumption, inadequate nutrition). Total CVRB in Croatia was 44.7% for men and 50.3% for women. Combining both high and moderate CVRB, men were found to be under more risk than women (72.8% vs. 61.7%, respectively). The result showed an east-north-west gradient in continental Croatia, with high CVRB in Eastern (40.2%) and Central region (44.3%), City of Zagreb (45.7%) and Northern region (53.1%). Mountainous region had the lowest prevalence of respondents with high CVRB (39.2%). Coastal region with the prevalence of 46.3% of high CVRB was nearly the same as the City of Zagreb. The results suggest the presence of substantial regional differences in the cardiovascular risk burden